The Relationship Between Spirituality Level and The Incidence of Depression: A Study on Eleventh-Grade Students at Pondok Al-Hidayat Islamic Boarding School Krasak Demak - Sulistiyowati, Linda; Fitrikasari, Alifiati; Wardani, Natalia Dewi; Sarjana, Widodo (Jurnal Psikiatri Surabaya, 2022)
ABSTRACT Background: The depression incidence around Southeast Asia in 2017 was 85.67 million cases (27%), and 7.5% of it occurred in the 15-19 years old age group. In Indonesia, the incidence of depression in 2017 was 9,162,886 cases (3.7%). Depression can be a major cause of disability and even lead to suicide, promoting many studies to find factors that can prevent depression in teenagers, one of which is related to the spirituality level. Objective: Determining the relationship between spirituality level and the incidence of depression. Methods: This study is a quantitative study with a cross-sectional study design. A total of 106 samples is included. They were eleventh-grade students who only studied Salaf and students who studied both Salaf and general sciences at the Al-Hidayat Islamic Boarding School Krasak Temuroso Guntur, Demak in the 2019-2020 school year. Data was collected using the Spirituality Orientation Inventory questionnaire and the Child Depression Inventory questionnaire, then analyzed using the Chi-square test. Results: The depression incidence among Al-Hidayat Islamic Boarding School students is 12%. Most students (93.5%) have a high spiritual level. There is a relationship between spirituality level and the incidence of depression in all eleventh-grade students, but no significant difference between spirituality level and the incidence of depression among the students who only study Salaf and the students who studied both Salaf and general sciences. Conclusion: The incidence of depression in Al-Hidayat Islamic Boarding School students is related to the spiritual level of students. Keywords: depression, teenager, students, spiritual level, Islamic boarding school